Evaluation of the program for modeling and implementation of a virtual laboratory for solid-state electronics - Suprapto, Yuyun; Pambudiyatno, Nyaris; Harianto, Bambang Bagus; Sabur, Fatmawati; Setiawan, Ariyono; Sazali, Abdul Muti (Faculty of Engineering, Universitas Negeri Yogyakarta, 2023)
During the Covid 19 pandemic, the teaching and learning process, especially in practical courses which were initially face-to-face, turned online. This change had several impacts on lectures, especially in terms of learning outcomes and the quality of graduates in terms of skills. Therefore, it is very necessary to carry out an evaluation of this learning process using the CIPP model developed by Stufflebeam. This evaluation model aims to find out how effective the use of virtual laboratories is in learning practical courses online. This research is evaluative research using a qualitative descriptive approach. Where the data used in this study is qualitative data with analytical methods. The technique used in this study is to examine existing data using grounded research methods. From the results of this study, there is the largest percentage, namely the use of virtual laboratories has been quite effective in online learning during the Covid-19 pandemic, with the improvement and development of media and learning models that are more innovative and creative. In addition, efforts in skills that directly deal with equipment still need to be fulfilled in real laboratories to increase enrichment and deeper understanding and skills in work procedures in the world of work later.